Comparative Study of Riddles with The Concept Profession in Uzbek and English Languages (Wire Insights: Journal of Innovation Insights, 2026)
This study presents a comparative analysis of riddles formed on the basis of the concept of profession in Uzbek and English folklore traditions. Riddles are examined as paremiological units that encode occupational identity through indirect nomination, functional semantics, and metaphorical representation. The research aims to identify universal cognitive mechanisms and culture-specific features in the linguistic modeling of professions